Infant gender‐based differentiation in concentration of milk fats using near infrared Raman spectroscopy. (13th October 2016) - Ullah, Rahat; Khan, Saranjam; Khan, Asifullah; Saleem, Muhammad; Ali, Hina; Bilal, Muhammad; Ahmed, Mushtaq
Abstract : This study demonstrates infant gender‐based differentiation in concentration of milk fats using Raman spectroscopy. In total, 50 buffalo milk samples have been used in this study, out of which 20 have male and 30 have female infant babies. These samples were collected from local farm houses in Islamabad, Pakistan. Raman spectra of milk samples contain peaks/bands at 762, 797, 868–890, 1063–1083, 1126, 1223, 1296, 1439, 1654 and 1744 cm −1 . Significant variation in peaks/bands at 1063–1083, 1296, 1438 and 1654 cm −1 corresponding to concentration of milk fats has been observed between buffalo milk for male and female infants. It shows that a buffalo with female infant produces comparatively high fat milk. The spectral difference has been further highlighted by applying principal component analysis (PCA)‐based algorithm on Raman spectra of the milk samples. It is observed that PCA is able to clearly separate the two sets of classes on the basis of features obtained from the Raman spectra. Additionally, more than 99.5% variance in the data has been explained by only the first five PC components. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Infant gender‐based differentiation in milk fat concentration has been studied using Raman spectroscopy. Variation in peaks/bands at 1063–1083, 1296, 1438 and 1654 cm −1 has been observed between buffalo milk for male and female infants. The results of the study show that buffalo with female infant produce higher fat milk as compared to male infant. PCA is also able to clearly separate the two sets of classes on the basis of features obtained from the Raman spectra.